2016
DOI: 10.1128/jvi.01751-15
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Sensor To Characterize Arenavirus Envelope Glycoprotein Cleavage by Subtilisin Kexin Isozyme 1/Site 1 Protease

Abstract: Arenaviruses are emerging viruses including several causative agents of severe hemorrhagic fevers in humans. The advent of next-generation sequencing technology has greatly accelerated the discovery of novel arenavirus species. However, for many of these viruses, only genetic information is available, and their zoonotic disease potential remains unknown. During the arenavirus life cycle, processing of the viral envelope glycoprotein precursor (GPC) by the cellular subtilisin kexin isozyme 1 (SKI-1)/site 1 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…The S segment encodes the viral glycoprotein precursor (GPC) and the nucleoprotein (NP). Cellular signal peptidase cleaves GPC into a stable signal peptide (SSP) and GP1/GP2, and cellular subtilase SKI-1/S1P further cleaves GP1/GP2 into the GP1 and GP2 subunits [11][12][13][14][15]. GP1, the N-terminal subunit, mediates cellular receptor binding and is also the target of host neutralizing antibodies [16].…”
Section: Introductionmentioning
confidence: 99%
“…The S segment encodes the viral glycoprotein precursor (GPC) and the nucleoprotein (NP). Cellular signal peptidase cleaves GPC into a stable signal peptide (SSP) and GP1/GP2, and cellular subtilase SKI-1/S1P further cleaves GP1/GP2 into the GP1 and GP2 subunits [11][12][13][14][15]. GP1, the N-terminal subunit, mediates cellular receptor binding and is also the target of host neutralizing antibodies [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we developed a cell‐based biosensor of the nonbasic PC SKI‐1/S1P that included an N‐terminal Gaussia luciferase (GLuc) reporter fused to a SKI‐1/S1P‐derived membrane anchor via a cleavable peptide sequence mimicking a physiological SKI‐1/S1P recognition site . Functional tests revealed that the sensor recapitulates key features of authentic substrates, including strict SKI‐1/S1P specificity and correct subcellular location of processing . Examination of a panel of SKI‐1/S1P sensors with different SKI‐1/S1P substrate‐derived sequences revealed that the cell‐based sensors accurately predicted SKI‐1/S1P cleavage efficiency of the authentic substrate .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the noncanonical nature of the basic PC recognition site in BPCS , specificity of furin cleavage was a major concern. In our previous studies with the analogous cell‐based SKI‐1/S1P sensor, we found that in vitro processing of peptides derived from recognition sequences of known SKI‐1/S1P substrates sometimes failed, whereas the exact same sequence underwent efficient cleavage in the context of the authentic substrate protein and the cell‐based sensor . Therefore, to validate the specificity of BPCS for furin in its cellular context, we first performed site‐directed mutagenesis of the sensor cleavage site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1P is perhaps emerging as a clinical target in diseases such as glioblastoma [4], hypercholesterolemia/cardiovascular disease [5,6], and more prominently as antiviral targets. Pharmacological agents with inhibitory actions on S1P have been shown to reduce dengue virus propagation [7,8], and arenaviral glycoprotein processing [9].…”
Section: Introductionmentioning
confidence: 99%